2008
DOI: 10.1016/j.cub.2008.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Podosomes Are Dynamic Mechanosensors

Abstract: Summary Podosomes are self-organized dynamic actin-containing structures that adhere to the extracellular matrix via integrins [1–5]. Yet it is not clear what regulates podosome dynamics and whether podosomes can function as direct mechanosensors like focal adhesions [6–9]. We show here that myosin IIs form circular structures outside and at the podosome actin ring to regulate podosome dynamics. Inhibiting myosin II-dependent tension dissipated podosome actin rings before dissipating the myosin ring structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 23 publications
7
114
0
Order By: Relevance
“…In Src-transformed cells, traction force microscopy revealed that invadosomes are mechanosensing structures, suggesting that localized mechanotransduction signaling through adhesions might control podosomes and/or invadopodia (Collin et al, 2008). Likewise, we found that ECM rigidity controls the activity, but not the formation of, invadopodia puncta .…”
Section: Regulation Of Invadopodia and Podosomes By Adhesion Protein mentioning
confidence: 53%
“…In Src-transformed cells, traction force microscopy revealed that invadosomes are mechanosensing structures, suggesting that localized mechanotransduction signaling through adhesions might control podosomes and/or invadopodia (Collin et al, 2008). Likewise, we found that ECM rigidity controls the activity, but not the formation of, invadopodia puncta .…”
Section: Regulation Of Invadopodia and Podosomes By Adhesion Protein mentioning
confidence: 53%
“…Our studies using AFM-enabled nanoindentation with an ILP-scaled probe suggest that T cell ILPs would experience changes in stiffness induced by barrier-altering stimuli. Although our studies do not assess whether T cell ILPs can serve as formal stiffness 'mechanosensors', invadosomes in other cell types have been shown to function as dynamic mechanosensors that sense and respond differentially to matrices of varied stiffness (AlbigesRizo et al, 2009;Alexander et al, 2008;Collin et al, 2008). Dynamic and ultra-structural imaging demonstrated that whereas ILPs were 'frustrated' when they encountered nuclear laminar and dense (cortical or central) F-actin bundles or meshwork, they exhibited an increased ability to distort the cytoskeleton and breach the endothelial barrier at regions of relatively lower Factin density.…”
Section: Tenertaxis -Probing For Barrier Weak Spotsmentioning
confidence: 99%
“…Indeed, we find here cells probing through a Cdc42/Rac1-and Arp2/3-mediated process (Carman, et al, 2007) of repeatedly extending and retracting ILPs in the direction normal to that of lateral migration in order to locally compress or push against (rather than pull on) the underlying cell substrate. Although podosomes have been suggested to be mechanosensitive (Albiges-Rizo et al; Alexander et al, 2008;Collin et al, 2008), it remains to be determined whether tenertaxis is a bona fide mechanosensing process or a more simply stochastic one, in which breaching is limited by the local ILP-stalling force of the substrate (i.e. stiffness) combined with the overall efficiency of probing and lateral migration.…”
Section: The Relationship Between Tenertaxis and Durotaxismentioning
confidence: 99%
“…Although this has not been widely investigated, at least two recent studies demonstrate that podosomes can serve as 'dynamic mechanosensors' (Collin et al, 2008;Collin et al, 2006). In these two studies, using polyacrylamide collagencoated substrates of defined rigidity, Collin et al demonstrated that the lifespan and density of fibroblast podosomes depended on substrate flexibility and that such mechanosensory properties were mediated in part through myosin-II motor proteins.…”
Section: Mechanotransduction By Ilps?mentioning
confidence: 99%